2008
DOI: 10.1359/jbmr.080408
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Bone Health: Impact of Moderately High and Low Salt Intakes on Calcium Metabolism in Postmenopausal Women

Abstract: ABSTRACT:High salt intake is a well-recognized risk factor for osteoporosis because it induces calciuria, but the effects of salt on calcium metabolism and the potential impact on bone health in postmenopausal women have not been fully characterized. This study investigated adaptive mechanisms in response to changes in salt and calcium intake in postmenopausal women. Eleven women completed a randomized cross-over trial consisting of four successive 5-wk periods of controlled dietary intervention, each separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 32 publications
1
92
1
1
Order By: Relevance
“…Vitamin D is a direct regulator of the metabolism of calcium and, partly, phosphate with feedback relationships encompassing bone, intestine and kidney (36). On the other hand, excessive sodium intake represents a recognised risk factor for development of osteoporosis (often associated with vitamin D deficiency) due to interference with the renal excretion of calcium (37). Psychotropic medications by themselves could cause sodium disturbances, primarily hyponatremia (16,17,40).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is a direct regulator of the metabolism of calcium and, partly, phosphate with feedback relationships encompassing bone, intestine and kidney (36). On the other hand, excessive sodium intake represents a recognised risk factor for development of osteoporosis (often associated with vitamin D deficiency) due to interference with the renal excretion of calcium (37). Psychotropic medications by themselves could cause sodium disturbances, primarily hyponatremia (16,17,40).…”
Section: Discussionmentioning
confidence: 99%
“…One of the noncontrolled Paleolithic diet-intervention studies also showed a decrease from baseline in calcium excretion after 10 d consumption of the Paleolithic diet (22). The low-salt, high-protein, and alkalizing properties of Paleo nutrition may substantially contribute to a healthy calcium balance (42)(43)(44).…”
Section: Safety Concernsmentioning
confidence: 98%
“…37 In both rats and man, marked Na + loading alone (for example, a 8% NaCl diet) is accompanied by hypercalciuria, SHPT with bone loss and a proinflammatory vascular phenotype. [42][43][44][45][46][47][48][49][50] The likely mechanism is thought to be related to an expansion of the extravascular space, resulting in decreased proximal tubular resorption and thereby increased distal delivery of Na + , Ca 2+ and Mg 2+ , with the mineralocorticoid promoting distal tubular Na + resorption without retarding Ca 2+ or Mg 2+ excretion. [32][33][34][35][36] This may be further accentuated by nitric oxide-mediated increments in medullary blood flow.…”
Section: Sodium: the Facilitator In Aldosteronismmentioning
confidence: 99%